Nail Plate Constructs: A Novel Technique for Treatment of Unstable Charcot Ankle and Hindfoot Deformity. Issue 4 (November 2022) - Boyer, Braden J.; Smith, Carson; Bettin, Clayton C.
Category: Hindfoot; Diabetes Introduction/Purpose: Charcot arthropathy is a disorder known to have poor outcomes with a high risk of amputation. Life expectancy, lifetime amputation rates and five-year mortality rates approach 50%. Patients often present with multiple medical comorbidities, poor bone quality and severe deformity. They have difficulty following non-weight bearing precautions postoperatively leading to fixation failure, recurrent instability and wound problems. Recent trauma literature has shown that a nail plate construct (NPC) provides a good option for elderly patients with poor bone quality sustaining distal femur fractures. This intervention has afforded these low demand patients increased stability allowing early weightbearing while maintaining good clinical results. Implementing this concept, we report early results with a novel application of NPCs in patients with charcot arthropathy of the ankle and hindfoot. Methods: Patients with Charcot arthropathy undergoing tibiotalocalcaneal fusion via combination of intramedullary nail fixation and lateral variable angle locked plating by a single surgeon from September 2020 to August 2021 were included in our study. Age, comorbidities, Hemoglobin A1c, smoking status, ambulatory status, presence of an ulcer, history of infection, implants used, bone graft used, tourniquet time, and postoperative complications were retrospectively recorded. Results: Four patients with hindfoot charcot deformities were included in our case series. Two men and two women with an average age of 58 years (range, 45-67 years) were treated. Three patients were diabetic with an average Hemoglobin A1C of 6.9 (range 5.2-10.7). Three patients had an active or impending ulcer. All patients were treated with a tibiotalocalcaneal variable angle locked plate around a hindfoot fusion nail with fibular autograft and biologic adjunct. Follow-up ranged from 4-12 months. All patients were made non-weight bearing, but all reported weightbearing in the perioperative period. Three of the four patients have a stable, non-infected, ulcer free foot and are ambulating in commercially available footwear (75% favorable outcome). One patient suffered a deep infection which was ultimately treated with below-knee amputation. This patient was morbidly obese, failed prior ORIF of the ankle, and was on vancomycin at time of presentation. Conclusion: Charcot arthropathy is a difficult pathologic process to treat surgically with high rates of complications. This difficult patient population often is unable to follow non-weight bearing precautions putting them at increased risk for failure. NPCs, as described in new trauma literature, promote encouraging results in patients with poor bone quality permitted early weight bearing. Hindfoot nail with variable angle locked plate combination for unstable ankle and hindfoot charcot arthropathy yields a 75% favorable outcome with early results consisting of 3 patients with functional limb salvage and 1 patient with below knee amputation.